The influence of marbling and maturity on beef tenderness - Tuma, H.J.; Grant, D.; Covington, R. (Kansas State University. Agricultural Experiment Station, 2011)
The beef carcass quality grading system currently used has been challenged by many who say current standards are too high and that the amount of marbling to attain a given grade should be decreased.
Keywords: Beef; Marbling; Maturity; Tenderness